Urea recovery from stabilized urine using a novel ethanol evaporation and recrystallization process - H. Marepula (Elsevier, 2021)
Urea is a raw material in the production of various chemicals and is a key nitrogen-based fertilizer. The conventional process to manufacture synthetic urea operates at high temperatures and pressures and is therefore energy intensive. The aim of this work was to investigate the feasibility of recovering and purifying urea crystals from human urine using a novel ethanol evaporation and recrystallization process that exploits the solubility differences of urea and impurities in water and ethanol. This approach could provide an alternative method to produce urea that operates at atmospheric pressure and low temperatures (< 30°C).Synthetic and real human urine was treated with Ca(OH)2 to prevent urea hydrolysis and then dried to recover the solids. These solids were dissolved in a predetermined amount of ethanol and the urea present was recrystallized. A complex synthetic urine solution (with various organics and inorganics) had a urea solubility of 56.7 g L−1 at 22°C. It was determined that the solubility of urea in ethanol increased when more organics were present in the solution. Urea was recovered from inorganic synthetic urine (SI), organic synthetic urine (SO) and real human urine (RU) with yields of 88%, 77% and 67%, respectively. The purity of urea increased from 41%, 41% and 43% to 91%, 76% and 76% for SI, SO and RU using the ethanol evaporation and recrystallization process.